Impact of frontline demonstrations on productivity and economics of rainfed pearl millet [(Pennisetum glaucum (L) R. Emend Stuntz] in western Rajasthan: FLD’s of pearl millet in western Rajasthan - Jat, Nand Kishore; Ola, C M; Avinashilingam, Vijay; Meghwal, P R; Parmender; Hajong, Dipika (Annals of Arid Zone, 2023)
Front-line demonstrations were carried out in ICAR-Farmer FIRST Project in different villages of Jodhpur (Rajasthan) from Kharif 2017 to 2020 to demonstrate the potential of improved crop production technologies of pearl millet for enhancing the crop productivity and farmers’ income. In ‘improved practices’ (IP) pearl millet hybrids like MPMH-17 and HHB-67(I) with or without the recommended dose of fertilizers (60 kg N + 30 kg P2O5/ha) were demonstrated with existing ‘farmer’s practice’ (FP) of pearl millet production. The grain yield in IP ranges from 13.6 to 16.4 q/ha whereas in FP it was in the range of 10.7 to 13.4 q/ha. The percent increase in grain yield with IP over FP was recorded in the range of 17.8 to 26.7% whereas the percent increase in stover yield was between 31.1 to 36.0%. An extension gap ranging from 2.06-3.07 q/ha was found between IP and FP during the different years. Both the technology gap (38.1-40.8 q/ha) and technology index (69.7-74.9) were higher with hybrid MPMH-17 irrespective of fertilizer application whereas, these were lowest with hybrid HHB-67(I). The highest increase in Net returns and added net returns were observed in improved hybrid MPMH-17 supplemented with fertilizers followed by improved hybrid HHB-67(I). However, the incremental cost-benefit ratio was recorded lower in HHB-67(I) than in MPMH-17. The improved hybrids MPMH-17 and HHB-67(I) performed better over the farmer’s practice indicating that for realizing profitable yield of pearl millet farmers should adopt improved cultivars and apply recommended dose of fertilizers for realizing the food security as well as helps in improving the economic and social status.